Financing of small and medium-sized enterprises on the example of bank loans - Sambór, Gabriela (SPC Journal of Education, 2020)
The main purpose of the article is to present the small and medium-sized enterprises sector, their size and the possibility of choosing individual sources of financing, and above all a brief presentation of bank loans. They constitute one of the largest and the most important sources of financing of external origin and are the main financing source of the majority of investments of an enterprise.Â